Automated design space exploration of multi-cycle transient fault detectable datapath based on multi-objective user constraints for application specific computing. (April 2015) - Sengupta, Anirban; Bhadauria, Saumya
Highlights: Novel exploration approach for multi-cycle transient fault detectable datapath. Novel mechanism for detecting multi-cycle transient fault. Performs tradeoff between power and execution delay. Provides an average improvement in QoR of >9% compared to[15] . Abstract: A novel automated design space exploration (DSE) approach of multi-cycle transient fault detectable datapath based on multi-objective user constraints (power and delay) for application specific computing is presented in this paper. To the best of the authors' knowledge, this is the first work in the literature to solve this problem. The presented approach, driven by bacterial foraging optimization (BFO) algorithm provides easy flexibility to change direction in the design space through tumble/swim actions if a search path is found ineffective. The approach is highly capable of reaching true Pareto optimal curve indicated by the closeness of our non-dominated solutions to the true Pareto front and their uniform distribution over the Pareto curve (implying diversity). The contributions of this paper are as follows: (a) novel exploration approach for generating a high quality fault detectable structure based on user provided requirements of power-delay, which is capable of transient error detection in the datapath; (b) novel fault detectable algorithm for handling single and multi-cycle transient faults. The results of the proposed approach indicated an average improvement in Quality of Results (QoR) of >9% and reduction in hardware usage of >23% compared to recent approaches that are closer in solving a similar objective.